2007
DOI: 10.1371/journal.pone.0000459
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Intraviral Protein-Protein Interactions of the SARS Coronavirus ORFeome

Abstract: The severe acute respiratory syndrome coronavirus (SARS-CoV) genome is predicted to encode 14 functional open reading frames, leading to the expression of up to 30 structural and non-structural protein products. The functions of a large number of viral ORFs are poorly understood or unknown. In order to gain more insight into functions and modes of action and interaction of the different proteins, we cloned the viral ORFeome and performed a genome-wide analysis for intraviral protein interactions and for intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
302
3
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(339 citation statements)
references
References 49 publications
29
302
3
5
Order By: Relevance
“…A large number of possible protein-protein interactions between coronavirus pp1a/pp1ab subunits have been identified in various in vitro studies and the data obtained are not consistent in all cases. [94][95][96] To further complicate things, protein-protein interactions may be transient, occurring only at specific steps in the viral life cycle, or have accessory rather than essential roles. The…”
Section: The Role Of Nendou In Nidovirus Replicationmentioning
confidence: 99%
“…A large number of possible protein-protein interactions between coronavirus pp1a/pp1ab subunits have been identified in various in vitro studies and the data obtained are not consistent in all cases. [94][95][96] To further complicate things, protein-protein interactions may be transient, occurring only at specific steps in the viral life cycle, or have accessory rather than essential roles. The…”
Section: The Role Of Nendou In Nidovirus Replicationmentioning
confidence: 99%
“…This section will delineate the scenario of protein interaction network analysis of some of these species including viruses, bacteria and protozoan parasites (Table 1). Amongst these, the topology of intra-viral networks of different members of herpesvirus family (viz., Kaposi's clustering coefficient and network diameter [76][77][78][79][80][81][82]. The analysis revealed that viral networks appear as single, highly coupled modules with relatively many hubs and few 'peripheral' nodes, in contrast to scale-free cellular networks having well-separated functional modules.…”
Section: Analyses Of Pathogenic Pins: Intra-and Interspecies Scenariomentioning
confidence: 99%
“…Yeast two-hybrid screening Human Fetal Brain Matchmaker cDNA library (Clontech, Palo Alto, USA) cloned into the vector pGADT7 was used to transfect the yeast strain Y187, and the transfected strain was used for two-hybrid screening [24]. The pGBKT7-FXR1 recombinant plasmid was transfected into the yeast strain AH109, which was then used as the bait to screen the library.…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%